Understanding the adopted child. (2nd September 2019) - Hajittofi, Nina
Abstract : Is there an invisible face of suffering when it comes to adoption? Nina Hajittofi explores the evidence for adoptees' hidden trauma and makes a powerful case for greater understanding of their experience and the need for more support from the professionals and family around them.